Two unusual complications of neuroleptic malignant syndrome - Ahmad, A. (Medknow Publications & Media Pvt Ltd, 2013)
Neuroleptic malignant syndrome (NMS) is a rare but well described complication of the administration of antipsychotic agents. Compartment syndrome, with increased pressures within the confined space of fascial sheaths leading to compression damage of the contained tissue, similarly is well described. Brachial plexus injuries caused by patient malposition are also very rare but a few cases have been reported. We report a case where these three complications occurred together. This was attributable to the patient developing NMS whilst asleep in the prone position overnight.